Matrix Isolation Photochemistry at Low Temperatures and Spectroscopic Properties of ã-Butyrothiolactone - Dugarte Jiménez, Nahir Yerely (2010)
The five-membered heterocyclic γ-butyrothiolactone was isolated in a low-temperature, inert Ar matrix, and the UV−visible (200 ≤ λ ≤ 800 nm)-induced photochemistry was studied. On the basis of the IR spectra, the formation of ethylketene (CH3CH2CH═C═O) was identified as the main channel of photodecomposition. The valence electronic structure was investigated by He(I) photoelectron spectroscopy assisted by quantum chemical calculations at the outer valence Green’s function/6-311++G(d,p) level of theory. The first three bands at 9.54, 9.69, and 11.89 eV are assigned to the nS, nO, and πC═O orbitals, respectively, denoting the importance of the −SC(O)− group in the outermost electronic properties. The conventional ring strain energy was determined to be 3.8 kcal mol−1 at the G2MP2 level of calculation within the hyperhomodesmotic model.